PENGARUH MODEL RECIPROCAL TEACHING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VII SMP NEGERI 6 PURWOKERTO - Artiah, Artiah; Untarti, Reni (AlphaMath : Journal of Mathematics Education, 2017)
This research aimed to determine whether the reciprocal teaching model affects the ability ofstudents’ mathematical representation or not. The research design used was post test onlycontrol design. Sampling used cluster random sampling by taking two classes namely, classVII B as the experimental class and class VII A as the control class. The location of theresearch was SMP Negeri 6 Purwokerto. As for obtaining data used post test the ability ofmathematical representation, the post test question in the form of description. Post test resultof mathematical representation ability showed experiment calss average was 65.23, whilecontrol class equal to 59.31. Also it obtained the score of hypothesis testing using independentsample t-test as follows, Sig. = 0.051/2 = 0.0255 with 0.05 which means Sig < 0.05 or 0 H isrejected. It can be concluded that the reciprocal teaching model affecs the ability ofmathematical representation.Keyword: Mathematical Representation Ability, Reciprocal Teaching.